Przykłady kooperatyw spożywczych w Polsce jako laboratorium inicjatyw społecznościowych - Skrzypczak, Bohdan (Kultura-Społeczeństwo-Edukacja, 2020)
The paper discusses new forms of social collaboration that have been actively developing in cities for a number of years now. The text analyses the form of social interactions that the author has defined as a community institution. Applying this cognitive category to a reflection on a specific example – a food cooperative – made it possible to capture the characteristic features of a community self-organisation mechanism. Discovering the institutional aspects of the discussed phenomenon made it possible to observe that community collaboration involves an educational process of constructing the common good and consequently – a major potential of pedagogical impact and significant impact on local public policies.